Efektivitas Guru Terhadap Pembelajaran Seni Teater pada Mata Pelajaran Seni Budaya di SMK Negeri 1 Benai - Indri, Yasrizal (Lembaga Bale Literasi, 2023)
This research addresses the following problems: (1) Planning in theater arts learning at SMK Negeri 1 Benai, (2) Conformity between plans and the process of learning theater arts at SMK Negeri 1 Benai, (3) The effectiveness of theater arts learning at SMK Negeri 1 Benai. The data collection techniques used are: literature study by reading several books and journals related to the research title. The results showed: (1) The planning for theater arts learning at SMK Negeri 1 Benai is not in accordance with the applicable curriculum standards in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 64 of 2013. (2) Conformity between the plan and the theater arts learning process at SMK Negeri 1 Benai is categorized as quite suitable. (3) The effectiveness of theater arts learning at SMK Negeri 1 Benai is less effective.